2022
DOI: 10.3389/fmicb.2022.841397
|View full text |Cite
|
Sign up to set email alerts
|

Portulaca oleracea Polysaccharides Modulate Intestinal Microflora in Aged Rats in vitro

Abstract: To explore the effect of Portulaca oleracea polysaccharides (POP) in regulating intestinal microflora in aged rats in vitro, its intestinal microbial composition was analyzed by 16 S rDNA high-throughput sequencing, and the level of short-chain fatty acids in fermentation broth was determined by LC-MS. POP significantly upregulated the relative abundance of Lactobacillus, Eggerthella, and Paraprevotella and significantly downregulated Escherichia_Shigella, Bacteroides, and Eubacterium nodatum groups. The pH va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…POL plays an extremely important role in life activities by lowering body glucose, eliminating body inflammation, changing intestinal morphology, improving growth performance, and antitumor effects [ 30 ]. Yi S et al found that Portulaca oleracea L. extract maintains the balance of intestinal flora by inhibiting Wnt/β-catenin signaling, which in turn inhibits colon cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…POL plays an extremely important role in life activities by lowering body glucose, eliminating body inflammation, changing intestinal morphology, improving growth performance, and antitumor effects [ 30 ]. Yi S et al found that Portulaca oleracea L. extract maintains the balance of intestinal flora by inhibiting Wnt/β-catenin signaling, which in turn inhibits colon cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that PO has neuroprotective, antibacterial, antidiabetic, antioxidant, anti-inflammatory, anti-ulcer and anticancer activities, and plays an important role in alleviating symptoms such as inflammation, fever, headache, and insomnia ( 22 , 23 ). Moreover, PO can regulate the gut microbiota, promote probiotics and inhibit pathogenic bacteria ( 24 ). Several studies have shown that PO has strong immunomodulatory effects, improving T-helper (Th) 1/Th2 and Th2/regulatory T (Treg) balance and reducing Ig E levels, thus exerting anti-inflammatory effects ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is one of the most important triggers of atherosclerosis in the arterial wall and ASCVD, which is characterized by abnormal elevated levels and deposition of apolipoprotein B, including LDL-C (20). Previous studies have shown that POP has biological properties, such as anti-tumor, anti-oxidation, anti-diabetes, anti-viral, and intestinal microbiota regulation (21)(22)(23)(24). Therefore, to investigate the mechanism by which purslane polysaccharides improve serum lipid levels in aging rats, we studied the intestinal metabolite profile and changes in the microbial community structure.…”
Section: Discussionmentioning
confidence: 99%